A Lipoxygenase from Red Alga Pyropia haitanensis, a Unique Enzyme Catalyzing the Free Radical Reactions of Polyunsaturated Fatty Acids with Triple Ethylenic Bonds - Zhu, Zhujun; Qian, Feijian; Yang, Rui; Chen, Juanjuan; Luo, Qijun; Chen, Haimin; Yan, Xiaojun (PLOS ONE, 2015)
Lipoxygenases (LOXs) are key enzymes to regulate the production of hormones and defensive metabolites in plants, animals and algae. In this research, a full length LOX gene has been cloned and expressed from the red alga Pyropia haitanensis (Bangiales, Rhodophyta) gametophyte (PhLOX2). Subsequent phylogenetic analysis showed that such LOX enzymes are separated at the early stage of evolution, establishing an independent branch. The LOX activity was investigated at the optimal pH of 8.0. It appears that PhLOX2 is a multifunctional enzyme featuring both lipoxygenase and hydroperoxidase activities. Additionally, PhLOX2 exhibits remarkable substrate and position flexibility, and it can catalyze an array of chemical reactions involving various polyunsaturated fatty acids, ranging from C18 to C22. As a matter of fact, mono-hydroperoxy, di-hydroperoxy and hydroxyl products have been obtained from such transformations, and eicosapentaenoic acid seem to be the most preferred substrate. It was found that at least triple ethylenic bonds are required for PhLOX2 to function as a LOX, and the resulting hydroxy products should be originated from the PhLOX2 mediated reduction of mono-hydroperoxides, in which the hydrogen abstraction occurs on the carbon atom between the second and third double bond. Most of the di-hydroperoxides observed seem to be missing their mono-position precursors. The substrate and position flexibility, as well as the function versatility of PhLOXs represent the ancient enzymatic pathway for organisms to control intracellular oxylipins.